Pengaruh Kualitas Pelayanan Karyawan Terhadap Keputusan Pembelian Pada Indomaret Bukit Sukasari Karawang - Raka, Alfin; Faddila, Syifa Pramudita (Business and Investment Review, 2023)
One of the determinants of purchasing decisions is the quality of service. The problem in this study is whether service quality influences purchasing decisions at Indomaret Bukit Sukasari Karawang partially and simultaneously. The purpose of this study was to determine the effect of service quality on purchasing decisions at Indomaret Bukit Sukasari Karawang partially and simultaneously. The variables in this study are service quality (X) and purchasing decisions (Y). data collection method used is a questionnaire. The data analysis method used is descriptive analysis and multiple linear regression analysis using SPSS 26. The results obtained are multiple linear equations KP = 0.589 + 0.794KPEL + ei. Partial test (t test) shows that service quality has a significant effect on purchasing decisions. Simultaneous test (f test) shows that service quality has a significant effect on purchasing decisions. The coefficient of simultaneous determination (R2) is 0.503, this means that 50.3% of purchasing decisions at Indomaret Bukit Sukasari Karawang are influenced by service quality while the rest are influenced by other variables outside the variables studied.